2020
DOI: 10.3946/kjme.2020.150
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the interprofessional education of the faculty and the level of interprofessional education competence of the students perceived by the faculty: a comparative study of medicine, nursing, and pharmacy

Abstract: Purpose: This study will compare differences in perception of interprofessional education (IPE) in the faculty of medicine, nursing, and pharmacy. It will also analyze differences in the level of importance of IPE competences and the present competence levels of their students perceived by the faculty. Methods: The study included 115 participants from the faculty of medicine, 31 from nursing, and 23 from pharmacy. The surveys contained 21 questions on their perceptions of IPE, and perception on the nine compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Hence, their interest in IPE is more insufficient. Meanwhile, a study on professors of medical, nursing, and pharmacy schools demonstrated that 85.2% of them did not know about IPE [20], which was similar to the proportion of students in this study. Such a low perception of IPE among the South Korean academia appears to have affected students' perception, as well.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Hence, their interest in IPE is more insufficient. Meanwhile, a study on professors of medical, nursing, and pharmacy schools demonstrated that 85.2% of them did not know about IPE [20], which was similar to the proportion of students in this study. Such a low perception of IPE among the South Korean academia appears to have affected students' perception, as well.…”
Section: Discussionsupporting
confidence: 80%
“…Survey of the perception of interprofessional education. To investigate students' perception of IPE, related literature was reviewed [20,34]. A total of 17 items were devised to explore the perception of IPE after the content validity was examined twice by two medical education specialists with IPE experience.…”
Section: Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…IPE programs in Korea operate in stark contrast to programs in Western countries. Recent studies examined the current condition of IPE implementation in medical schools [12] and perception of health care professionals and professors [7,[12][13][14]. According to these studies, 14.8% of professors in schools of medicine, nursing, and pharmacy were familiar with IPE and only 4.2% had experienced IPE.…”
Section: Introductionmentioning
confidence: 99%